Organoleptic Test Jengkol Kabau Seeds (Archidendron bubalinum (Jack) I. C Nielsen.) Fermented Products - Rani Zahara; Dezi Handayani (Serambi Biologi, 2020)
Rani Zahara, Dezi Handayani Jurusan Biologi FMIPA Universitas Negeri PadangJl. Prof. Dr. Hamka Air Tawar Barat Padang Email: Ranizahara28@gmail.comAbstract. Jengkol kabau seeds contains a high protein which can be used as a raw material for fermentation using tempe yeast. This research aims to find out the opinions of respondents on the taste of jengkol kabau seeds fermented using tempe yeast. The parameter used in this research to test the taste of the jengkol kabau fermented which are color, texture, smell and taste. The method used for organoleptic test is hedonic test (preference test). This test involved 10 people who like jengkol kabau seeds and 10 people who dont like jengkol kabau seeds. Organoleptic test data are gotten and presented in the form of a percentage of preference as follows for color 76% (like), texture 86% (so like), smell 80% (like), taste 94% (so like). While those who dont like the jengkol kabau seeds give an average percentage pf preference as follows for color 74% (enough like), texture 76% (like), smell 46% (dont like), taste 48% (dont like). Therefore, it can concluded that the jengkol kabau enthusiasts can recelve fermented jengkol kabau for all test categories, while respondents who dont like jengkol kabau are relatively not able to accept it.   Key word: Jengkol kabau seeds, Fermentation, Organoleptic test.